Air-induced collisional parameters in the ν3 band of methane. (November 2021) - Farji, A.; Aroui, H.; Vander Auwera, J.
Highlights: Multispectrum analysis of P, Q and R branch lines of the ν 3 band of 12 CH 4 in air. Modeling with a hard collision Dicke narrowed line shape and Rosenkranz line mixing. Room temperature measurements for 166 methane lines. Broadening, shift, narrowing and first-order line mixing coefficients reported. Graphical abstract: Abstract: Air broadening and shift coefficients together with narrowing and first order line mixing parameters were measured for 166 lines belonging to J ″ manifolds of the P ( J ″ = 2 − 11 ), Q ( J ″ = 1 − 12 ) and R ( J ″ = 0 − 11 ) branches of the ν 3 band of 12 CH 4 near 3.3  μ m. These measurements were carried out using a non-linear multispectrum least squares fitting technique. A hard collision Dicke narrowed line shape model including Rosenkranz line mixing was applied. Five high resolution Fourier transform spectra were recorded at room temperature, one at low pressure with pure methane and four at pressures up to 904 hPa with mixtures of methane and air. The measured parameters are compared with data available in the literature.